Production practices and labour utilization pattern of sugarcane production as monoculture and intercrop (Bangladesh Journal of Agricultural Research, 2007)
The present study was undertaken to find out the production practices and labour utilization pattern of producing sugarcane both as monoculture and as intercrop. Data were collected from 70 sugarcane producers of Kushtia District. The farmers produce sugarcane as monoculture and as intercrop with lentil, maize, potato, wheat, sunflower, and onion. Large farmers were more interested to produce sugarcane as intercrop than the medium and small farmers. High land and loamy soil was mostly used for producing sugarcane both as monoculture and as intercrop. ISD 16 was the most popular variety of sugarcane. Row to row distance was higher for intercropping than the sole sugarcane cultivation. The labour utilization was higher for producing sugarcane as intercrop than as monoculture. In Bangladesh, family labour was highly underused and some disguised unemployment is also present. In this situation, if intercropping with sugarcane is popularized then the unemployment situation may be improved as well as optimum utilization of family labour may be ensured. Bangladesh J. Agril. Res. 32(2) 2007: 307-321.